NetSuite for Consultants : a Handbook for ERP and CRM Consultants to Implement NetSuite 2021 Quickly and Easily. - Ries, Peter (Packt Publishing, Limited, 2022)
Get hands-on with NetSuite implementation, customization, and integration services for automating operations and accelerating business growth Key Features Understand how to take a new client from the kickoff meeting through to their go live and beyond in the fastest possible time Explore the new innovations in NetSuite 2021 and leading practices for ERP and CRM consultants Avoid the common pitfalls that consultants can run into when implementing NetSuite Book Description Used by thousands of organizations worldwide, NetSuite's customer and financial management solutions expedite daily financial transactions, accelerate the financial close, ensure compliance, and so much more. With companies around the world choosing to run their business on this cloud-based SaaS solution, the demand for NetSuite professionals is ever increasing. This book takes a hands-on approach to help you grasp the implementation and associated methodologies in no time. You'll start by exploring what NetSuite is, how it works, and how accounts, support, and updates work within its ecosystem. Understanding a business' requirements is a critical first step toward completing any software product implementation, so you'll learn how to write business requirements by learning about the various departments, roles, and processes in the client's organization. Once you've developed a solid understanding of NetSuite and your client, you can apply your knowledge to configure accounts and test everything with the users. Finally, you'll get to grips with managing both functional and technical issues that arise post-implementation and learn how to handle them like a professional. By the end of this book, you'll have gained the knowledge necessary to implement NetSuite for businesses and get things up and running in the shortest possible time. What you will learn Understand the NetSuite ecosystem, including its main modules, the platform, and related features Explore the fundamentals of NetSuite and get ready to implement it in any organization Discover how to manage gaps, data migration, and integrations with NetSuite Find out how to minimize disruptions in finance as you migrate to NetSuite Understand the steps to configure your organization's account and how development and testing fit into the implementation schedule Refine your skills with NetSuite tips and tricks and make each implementation process a success Who this book is for This book is for consultants (or any NetSuite users) tasked with bringing an organization live on NetSuite. Basic NetSuite training and a general understanding of its features is required to get the most out of this book.